Hypoxia and dissolved oxygen trends in the northeastern Adriatic Sea (Gulf of Trieste). (June 2019) - Kralj, M.; Lipizer, M.; Čermelj, B.; Celio, M.; Fabbro, C.; Brunetti, F.; Francé, J.; Mozetič, P.; Giani, M.
Abstract: Physical and chemical data collected in three stations, with time series ranging from 1983, 1986 and 1989 to 2016, were analyzed in order to detect trends and frequency of occurrence of hypoxia events in bottom waters of the Gulf of Trieste (Adriatic Sea). The results of the analysis of 30-years data show a tendency toward increasing oxygen concentration in the bottom waters, nevertheless two hypoxic events were recorded during the summers of 2015 and 2016 even in a relatively shallow area of the Gulf. The spatial and temporal extent of these events was analyzed by coupling oceanographic surveys with automatic oceanographic measurements. During both summers, the area was characterized by high seawater temperature (up to 28.4 °C at the surface) and salinity (38.1 at the bottom) and a marked stratification of the water column, which prevented the mixing of oxygen-rich surface water with oxygen-poor deep water. The main contribution to oxygen depletion in the bottom waters was attributed to plankton respiration (54–61%) and to benthic oxygen consumption (39–46%), which exceeded the oxygen produced by planktonic and benthic microalgae and the one diffused from the overlying oxygenated water. These events of marked oxygen depletion in shallow coastal ecosystems are possibly favored by the positive temperature trend in bottom waters, coupled with the increase in riverine discharges in late spring, limiting vertical mixing and bottom water renewal.